2015
DOI: 10.1007/s10877-015-9803-7
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of extravascular lung water using the transpulmonary ultrasound dilution (TPUD) method: a validation study in neonatal lambs

Abstract: Increased extravascular lung water (EVLW) may contribute to respiratory failure in neonates. Accurate measurement of EVLW in these patients is limited due to the lack of bedside methods. The aim of this pilot study was to investigate the reliability of the transpulmonary ultrasound dilution (TPUD) technique as a possible method for estimating EVLW in a neonatal animal model. Pulmonary edema was induced in 11 lambs by repeated surfactant lavages. In between the lavages, EVLW indexed by bodyweight was estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In future studies, the scoring system developed specifically for COVID-19 PN will be applied as suggested by Perrone et al [37]. In addition, the proposed technique needs to be improved with validation on reliable gold standard, e.g., using the postmortem gravimetry in animal studies or with the thermodilution in human studies as the reference in the future [20], [38].…”
Section: Limitations and Future Studymentioning
confidence: 99%
“…In future studies, the scoring system developed specifically for COVID-19 PN will be applied as suggested by Perrone et al [37]. In addition, the proposed technique needs to be improved with validation on reliable gold standard, e.g., using the postmortem gravimetry in animal studies or with the thermodilution in human studies as the reference in the future [20], [38].…”
Section: Limitations and Future Studymentioning
confidence: 99%
“…Some of these technologies require the placement of an arterial line (pulse contour and pulse power analysis) and may need placement of a central venous line for calibration purposes ( 7 ). These technologies have been poorly studied in the neonatal population whilst others are still under development (transpulmonary ultrasound dilution) ( 10 ). Most other CO measurement technologies in neonates offer only intermittent measurement values as they are labor, skill or technology intensive [transthoracic echocardiography (TTE) and cardiac magnetic resonance imaging (cMRI)] ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…While developing working prototypes, thorough testing in a simulated environment with computer models and high-fidelity physical manikins is highly recommended. After such technical validation, animal experiments in established animal models (12,14,(39)(40)(41)(42)(43) can confirm the feasibility to promote a clinical trial.…”
Section: Pls Technology Research and Developmentmentioning
confidence: 92%